DAMPAK PEMBERDAYAAN DESA WISATA HALAL - Rahmat Ridwan; Ratna Dewi (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2021)
A tourist village is a rural area that offers authenticity both in terms of socio-culture, customs, everyday life, traditional architecture and village spatial structure. The purpose of this study is to find out government policies, changes in people's attitudes and the impact felt on community empowerment. The method used in this research is a qualitative research with descriptive method. The results of the study show that first, the village government's policy towards community empowerment is carried out in the form of empowerment programs such as halal tourism villages, sheep manure management, bamboo management, plastic waste management. Second, the change in attitude that occurred in the community after the existence of the Cibuntu halal tourism village program, the community learned to maintain local culture and wisdom so that it became an attraction for tourists, so that changes in community behavior appeared in a more positive direction such as mutual cooperation, courtesy, hospitality, extra care cleanliness and become more religious than before. Third, the impact felt by the community is very positive, especially towards improving the economy and the community taking part in the empowerment process and management